TINJAUAN EKONOMI SYARIAH TERHADAP STRATEGI BISNIS UNIQ DRINK HEALTHY HERBAL DRINK KOTA LHOKSEUMAWE - Hidayatina Hidayatina; Suci Lailatul Laila (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2021)
The driving factor for the increased consumption of herbal medicine is the widespread issue of back to nature voiced by the international media. UniQ Drink Healthy Herbal Drink is a contemporary herbal drink from Central Java, which found an innovation with a traditional concept to become modern. The large number of herbal drink enthusiasts has attracted the attention of Mrs. Adis to become an entrepreneur in the herbal drink UniQ Drink Healthy Herbal Drink in the city of Lhokseumawe. The objectives of this research are: To examine the business strategy of UniQ Drink Healthy Herbal Drinks in general and based on a sharia economic perspective? The method used is in the form of field research with a qualitative descriptive approach. The results of this study explain that: a) UniQ Drink's business strategy is in accordance with the production and marketing strategy, in its production strategy the company does not use chemicals and preservatives and its management is still traditional. b) This business has not implemented a business strategy in accordance with Islamic law, including the facts that are not in the packaging label which are not indicators of production and expiration dates and in financial records, but the company always gets out of the amount earned by 20% of the amount obtained to give to the people.